1990
DOI: 10.1037/0022-0167.37.1.33
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of feminist and nonfeminist women's reactions to variants of nonsexist and feminist counseling.

Abstract: We were concerned with client-counselor matching along the dimension of attitudes toward feminism. We hypothesized that feminist subjects would be more receptive to the radical feminist counselor, whereas nonfeminist subjects would rate the nonsexist and liberal feminist counselor more positively. College women (N = 150) viewed 12 videotaped counseling vignettes that were varied by the feminist orientation of the counselor and the explicitness of the counselor's value statement about her approach in 2 replicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
53
3
1

Year Published

1991
1991
1996
1996

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(62 citation statements)
references
References 23 publications
5
53
3
1
Order By: Relevance
“…Results of the Enns and Hackett (1990) study demonstrated that radical and liberal feminist counselors were perceived as more trustwor-thy, expert, and helpful than was a nonsexist-humanistic therapist. Women indicated higher levels of willingness to see radical and liberal feminist counselors than a nonsexist counselor for career and sexual harassment concerns and equal levels of willingness to see all three counselors for personal and interpersonal concerns.…”
mentioning
confidence: 96%
See 4 more Smart Citations
“…Results of the Enns and Hackett (1990) study demonstrated that radical and liberal feminist counselors were perceived as more trustwor-thy, expert, and helpful than was a nonsexist-humanistic therapist. Women indicated higher levels of willingness to see radical and liberal feminist counselors than a nonsexist counselor for career and sexual harassment concerns and equal levels of willingness to see all three counselors for personal and interpersonal concerns.…”
mentioning
confidence: 96%
“…In an attempt to gain a more comprehensive view of how potential clients perceive feminist counselors, Enns and Hackett (1990) examined women's reactions to videotaped role plays of three approaches to counseling: nonsexist-humanistic, liberal feminist, and radical feminist. Past research has treated feminist counseling as a monolithic approach and may have obscured important differences between forms of feminist counseling.…”
mentioning
confidence: 99%
See 3 more Smart Citations